The pursuit of non-trade policy objectives in EU trade policy - Borchert, I; Conconi, P; Di Ubaldo, M; Herghelegiu, C (Cambridge University Press, 2021)
The European Union (EU) often conditions preferential access to its market on compliance with Non-Trade Policy Objectives (NTPOs), including human rights and labor and environmental standards. In this paper, we first systematically document the coverage of NTPOs across the main tools of EU trade policy: its (association and non-association) trade agreements and Generalized System of Preferences (GSP) programs. We then discuss the extent to which the EU can use these tools as a ‘carrot-and-stick’ mechanism to promote NTPOs in trading partners. We argue that, within trade agreements, the EU has limited scope to extend or restrict tariff preferences to ‘reward good behavior’ or ‘punish bad behavior’ on NTPOs, partly because multilateral rules require members to eliminate tariffs on substantially all trade. By contrast, GSP preferences are granted on a unilateral basis, and can thus more easily be extended or limited, depending on compliance with NTPOs. Our analysis also suggests that the commercial interests of the EU inhibit the full pursuit of NTPOs in its trade agreements and GSP programs.